A 125 million-year-old freshwater isopod shines new light on the origin of subterranean freshwater species - Mario Schädel; Dany Azar; Layla El Hajj; Sibelle Maksoud; Ninon Robin (Royal Society Open Science)
Here, we report fossil isopods preserved in laminated oil-shale mudstone (dysodile) from the Lower Cretaceous of Lebanon (Lower Barremian, 125 Ma, Grès du Liban Alloformation, Jezzine District). Based on a variety of proxies, their palaeoenvironments are determined to have been a shallow freshwater lake. The fossil isopods were studied using modern imaging techniques, such as multispectral imaging and photometric stereo, allowing for a detailed comparison of these specimens with comparable extant and fossil taxa. The conspecific fossils are herein recognized as remains of a new species—†Dysopodus gezei gen. et sp. nov.—of uncertain affinity within Cymothoida and bearing a strong resemblance to its non-parasitic lineages (Cirolanidae). A conspicuous pleotelson and uropod morphology set it apart from most species, with the notable exception of †Pseudoplakolana chiapaneca gen. nov. et comb. nov. from the Cretaceous of Mexico, originally attributed to an Australasian lineage (herein disputed). So far, the biogeographical distribution of the peri-Mediterranean underground fauna has predominantly been explained through a passive isolation process of former marine species, driven by regressing coastlines. Stemming from a freshwater lake environment, the 125 million-year-old fossils from Lebanon provide an unconventional perspective on the evolutionary origin of extant cave- and groundwater-dwelling cymothoidans.